Freemasonry’s Symbols in Dan Brown’s The Lost Symbol - M. IZZA TURACHMAN (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2015)
AbstrakKarya tulis ini membahas Freemasonry, Simbol-simbolnya, dan keberadaan simbol-simbol Freemasonri di gedunggedungbersejarah Washington DC seperti yang diungkap pada novel ini. Pembahasan ini fokus pada dua masalahutama, (1) Bagaimana simbol-simbol Freemasonry digambarkan pada novel ini, dan (2) apa hubungan antara simbolsimbolFreemasonry dan gedung-gedung bersejarah seperti yang digambarkan dalam novel. Simbol-simbol Freemasonripada novel Dan Brown The Lost Symbol sangat menarik dianalisa dengan menggunakan pendekatan semiotik. Artisemiotic adalah teori umum mengenai tanda-tanda dan simbol-simbol. Semiotik lebih memperhatikan makna pesan dancara pesan disampaikan melalui tanda-tanda dan simbol-simbol. Terdapat lima simbol utama yang ditunjukkan penulisuntuk pembaca. Melalui simbol-simbol tersebut mereka akan mengetahui pemikiran penulis bagaimana dia memandangdunia dan bagaimana dia berpikir mengenai tindakan dan objek-objek umum. Brown menggunakan The Chamber ofReflection, The hand of Mysteries , The Double-headed Eagle, The Masonic Ring , dan The Masonic Pyramid untukmenceritakan tentang Freemasonri. Simbol-simbol tersebut menggambarkan identitas Freemasonri sehingga pembacadapat mengerti dengan jelas apa dan bagaimana Freemasonri itu. Freemasonri mempunyai banyak rahasia-rahasia yangtersimpan pada simbol-simbol yang diciptakannya. Selanjutnya simbol-simbol tersebut juga muncul di arsitekturgedung-gedung bersejarah Washington DC misalnya The House of Temple, The US Capitol Building, dan GeorgeWashington Masonic Memorial. Di novel ini, Brown membangkitkan rasa ingin tahu pembaca dengan menciptakanmisteri-misteri di balik simbol-simbol tersebut. Dia selalu memberikan dorongan dan pengetahuan baru sehinggapembaca akan membaca novelnya hingga akhir. Mereka akan mempunyai kesan mendalam tentang novel yang merekabaca.Kata Kunci : Simbol-simbol,Freemasonri, Gedung-gedung bersejarah.AbstractThis paper deals with Freemasonry, its symbols, and the existence of Freemasonry’s symbols in Washington DChistorical buildings as revealed in the novel. Thus this study focuses on two major problems, (1) How is Freemasonry’ssymbols described in the novel, and (2) What is the relationship between Freemasonry’s symbols and historicalbuildings in Washington DC as reflected in the novel. Freemasonry’s symbols Dan Brown’s The Lost Symbol is veryinteresting to be analyze d by using semiotic approach. This approach is defined as a general theory of signs andsymbols . It more concerns to the meaning of the message and how the message is delivered to signs and symbols.Thereare five main symbols which the writer shows to the readers. Through the symbols they will know the writer’s mind onhow he views the world and how he thinks of common objects and actions. Brown takes The Chamber of Reflection,The hand of Mysteries , The Double-headed Eagle, The Masonic Ring , and The Masonic Pyramid to tell aboutFreemasonry. Those symbols represent Freemasonry’s identity. The readers can gain clearly the ideas of what and howFreemasonry is. It has a lot of secrets in the symbols which it creates. Furthermore those Freemasonry’s symbols appearin the architecture of historical buildings in Washington DC such as The House of Temple, The US Capitol Building,and George Washington Masonic Memorial. In this novel, Brown evokes the readers curiosity by creating mysteriesbehind the symbols. He always gives impulse and new knowledge, so that the readers will read the novel till the end.They have certain impression about the novel which they read.Keywords : Symbols, Freemasonry, Historical Buildings